Long non-coding RNA AFAP1-AS1 accelerates the progression of melanoma by targeting miR-653-5p/RAI14 axis - Fei Liu (BMC Cancer, 2020)
Abstract Background Melanoma is the most aggressive skin cancer that derived from pigment cells, accounting for the majority of the skin-cancer-related deaths. Despite great development and evolution have been made in surgery, radiotherapy and adjuvant chemotherapy, the prognosis of melanoma patients exhibited no significant improvement. Long noncoding RNAs (lncRNAs) are frequently dysregulated and involved in the development of cancers. LncRNA AFAP1-AS1 has been explored in various cancers, whereas its role and regulatory mechanism in melanoma are not well understood. Methods The expression of AFAP1-AS1 was detected by qRT-PCR. CCK-8, colony formation, transwell and western blot assays were performed to investigate the biological role of AFAP1-AS1 in melanoma. Male BALB/c nude mice were applied for in vivo experiments. The interaction among AFAP1-AS1, miR-653-5p and RAI14 was investigated by RNA pull down, RIP and luciferase reporter assays. Results AFAP1-AS1 was highly expressed in melanoma cell lines. Suppression of AFAP1-AS1 impaired cell proliferation, migration, invasion and EMT in melanoma. Moreover, AFAP1-AS1 was a ceRNA of RAI14 by competitively binding with miR-653-5p. Besides, miR-653-5p overexpression or RAI14 inhibition could repress tumor growth. Eventually, rescue assays indicated that the function of AFAP1-AS1 in the cellular process of melanoma was dependent on miR-653-5p and RAI14. Conclusions AFAP1-AS1 exerts its oncogenic function in melanoma by targeting miR-653-5p/RAI14 axis.